2009
DOI: 10.4103/0973-1075.53508
|View full text |Cite
|
Sign up to set email alerts
|

Dental expression and role in palliative treatment

Abstract: World Health Organization defines palliative care as the active total care of patients whose disease is not responding to curative treatment. Palliative care for the terminally ill is based on a multidimensional approach to provide whole-person comfort care while maintaining optimal function; dental care plays an important role in this multidisciplinary approach. The aim of the present study is to review significance of dentist's role to determine whether mouth care was effectively assessed and implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 6 publications
1
80
0
1
Order By: Relevance
“…For example, iron has been inserted into a substituted helicene in analogy with ferrocene, [51,52,53] and alkali metal ions have been suggested to form stable complexes with the helicenes. [54] It has also been suggested that suitable substitutions of the hydrogen atoms of the terminal aryl groups could allow for transition metal complexation between the added functional groups. [55,56] Other related compounds include heterohelicenes that bind to a metal ion which is located at the center between the surrounding helicene backbone, [57] and bis-helicene metal ion complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, iron has been inserted into a substituted helicene in analogy with ferrocene, [51,52,53] and alkali metal ions have been suggested to form stable complexes with the helicenes. [54] It has also been suggested that suitable substitutions of the hydrogen atoms of the terminal aryl groups could allow for transition metal complexation between the added functional groups. [55,56] Other related compounds include heterohelicenes that bind to a metal ion which is located at the center between the surrounding helicene backbone, [57] and bis-helicene metal ion complexes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many trainees do not view palliative care medicine as core clinical competencies. These attitudes coalesce into practice pattern that tend to devalue the provision of palliative care are the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care is defined by the WHO as "the active total care of the patient whose disease is not responsive to curative treatment". [1] Palliative care is a specialized area of healthcare which focuses on relieving and preventing the suffering of patients. Patients with oral cancer often have a complex and prolonged course of illness due to both the patterns of disease recurrence and the adverse effects of treatments that is marked by periods of freedom from disease and symptoms interspersed with bouts of serious illness, debility, and numerous physical and psychological symptoms including pain, dysphagia, disfigurement, weight loss, depression, and xerostomia.…”
Section: Introductionmentioning
confidence: 99%